CORAK HERMENEUTIKA AL MAWARDI DALAM KITAB AL-NUKAT WA AL ‘UYŪN - Anam, Syariful (UIN Raden Mas Said Surakarta, 2023)
The discourse of hermeneutics (interpretation) of the Qur'an becomes an interesting and factual study. Examining one of the monumental works of the Mufassir figures that should be taken into account is Shaykh al Mawardi. He is not only a bureaucrat who served as a Supreme Judge but also a Mufassir who should be used as a reference in ideas and thoughts. Through the work of al-Nukat wa al-'Uyūn, al Mawardi tries to offer a style of interpretation that combines the method of history (Naql) by involving linguistic reviews, grammar and jurisprudence, while the other side al Mawardi also used ijtihadi method (khalaf) by quoting and comparing the opinions of Mufassir. These two double steps are the distinction from other Mufassir, so the author tries to present and disseminate the style of interpretation of al Mawardi. This research is a literature study of the work of tafsir al Mawardi through a review of descriptive analysis of his interpretation method. The findings in the study indicate that al Mawardi has a distinctive method, namely the style of interpretation that tries to accommodate classical and contemporary models of interpretation (Ijtihādi) by citing some opinions of previous Mufassir and Fuqohā'.